PENGARUH COUNTRY ORIGIN, BRAND IMAGE DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MAKANAN PADA APLIKASI GRAB DI UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA PADA MASA PANDMI COVID-19 - Arif, Muhammad; Sari, Sufitri Mulia (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
The aim of this research is to analyze several things, namely: The influence of Country Of Origin on Purchasing Decisions, Brand Image on Purchasing Decisions and Service Quality on Purchasing Decisions, The Influence of Country Of Origin, Brand Image and Service Quality on Purchasing Decisions. In this study using 91 respondents who are students of the Faculty of Economics and Business management who use the grab application at the Muhammadiyah University of North Sumatra. The data collection technique used a list of statements such as online questionnaires and data analysis techniques used Statistical Package for The Social Sciences (SPSS) to test the four hypotheses proposed in this study. The results showed that: (1) Country Of Origin partially had a positive and significant effect on Purchasing Decisions (2) Brand Image Partially had a negative and insignificant effect on Purchasing Decisions (3) Partially Service Quality had a positive and significant effect on Purchasing Decisions (4) ) Country of Origin, Brand Image and Service Quality partially have a positive and significant effect on purchasing decisions.